Incidence of retained biopsy specimens after esophagogastroduodenoscopy and colonoscopy - Toy, Gregory; Colletier, Keegan; Hale, Gillian; Valentine, John; Gawron, Andrew J; Sossenheimer, Michael; Peterson, Kathryn; Aparicio, Rodrigo; Fang, John C (Endoscopy International Open, 2023)
Background and study aims In gastrointestinal endoscopy, biopsies must transit through the accessory channel and cap, presenting an opportunity for loss of tissue. We sought to determine the incidence of specimen retention in the accessory channel or cap and identify procedure characteristics associated with specimen retention.Patients and methods After completion of standard endoscopic procedures in which biopsies were obtained, the biopsy cap and accessory channel were inspected, brushed, and irrigated for any retained biopsy specimens according to a standard protocol. For controls, the same protocol was applied to procedures in which biopsies were not obtained. Specimen bottles from the recovery protocol were sent for pathological examination regardless of whether any visible tissue was present.Results A total of 216 outpatient procedures were included: 55 esophagogastroduodenoscopies (EGDs) and 50 colonoscopies in which biopsies were obtained and 56 EGDs and 55 colonoscopies in the control group. Retained specimens were found in either the cap or channel in 50 of 105 (48%). In 20 of 105 (19%), retained specimens were found just in the cap, in six of 105 (5.7%), retained specimens were found just in the channel, while in 24 of 105 (23%), retained specimens were found in both the cap and channel. Retained specimens were more likely to be found in EGDs compared to colonoscopies (58% vs. 36%, P = 0.031). No retained specimens were found in the control group.Conclusions Retained specimens are startingly common in standard gastrointestinal endoscopic procedures and could potentially change diagnoses and management. Quality improvement measures should be instituted to monitor prevalence of retained biopsies and methods to prevent them should be developed.